Current Approach in Radiation Therapy for Prostate Cancer - ALSAN ÇETİN, İLKNUR (GALENOS YAYINCILIK, 2020)
Prostate cancer is one of the most common malignancies in men. Radiotherapy is one of the main treatment modalities in the treatment of prostate cancer. The reflection of technological advances in the field of radiation oncology enables the safe application of higher doses of radiotherapy in the treatment of prostate cancer. In addition, improvements in normal tissue preservation are reflected in patients' quality of life. Radiotherapy can be applied in all stages of prostate cancer and postoperative radiotherapy can be applied in appropriate indication. Side effects are expected to be observed more in patients undergoing postoperative radiotherapy. The treatment decision should be based on personal preference after informing the patient about the advantages and disadvantages of each treatment approach.
Keywords: Prostate cancer; radiotherapy; treatment; TERM ANDROGEN DEPRIVATION; RATE BRACHYTHERAPY BOOST; PHASE-III TRIAL; RANDOMIZED-TRIAL; DEFINITIVE RADIOTHERAPY; ADJUVANT RADIOTHERAPY; RADICAL PROSTATECTOMY; DOSE-ESCALATION; OPEN-LABEL; FOLLOW-UP